Pengaruh Kompensasi Terhadap Kinerja Guru di SMP Negeri 1 Jombang - Siti Zuliani; Tri Suharti (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
This research aims to determine compensation, teacher performance and the influence of compensation on teacher performance at SMP Negeri 1 Jombang. This is because providing compensation to teachers can also improve teacher welfare and have an impact on teacher performance. Maximum compensation will influence the degree of teacher satisfaction in carrying out their duties and responsibilities. In the research, quantitative research was used with a survey design, while the data collection technique used a questionnaire with Spearman rank correlation data analysis techniques. The results of the research are: 1. Teacher compensation at SMP Negeri 1 Jombang is included in the medium category, with an average score (Mean) of 74. 2. Teacher performance at SMP Negeri 1 Jombang is included in the medium category, with an average score (Mean) is 75. 3. There is a relationship between compensation (variable X) and teacher performance (variable Y) based on the obtained value of Sig. (2-Tailed) is 0.041 < 0.05, while the correlation coefficient value is 0.264 which is in the interval 0.2 - 0.399 with the direction and relationship of the two variables being in the same direction and having a positive value. This shows that if compensation is increased, teacher performance will increase.